Hepatocellular carcinoma in patients cured of chronic hepatitis C: Minimal steatosis - Chiara Rocha; Erin H. Doyle; Chip A. Bowman; M‐Isabel Fiel; Ashley E. Stueck; Nicolas Goossens; Kian Bichoupan; Neal Patel; James F. Crismale; Jasnit Makkar; Sara Lewis; Ponni V. Perumalswami; et al. (Cancer Medicine, 2023)
Abstract Background Successful treatment of hepatitis C reduces liver inflammation and fibrosis; however, patients remain at risk of developing hepatocellular carcinoma (HCC). Aims To identify risk factors for new‐onset HCC in patients cured of hepatitis C. Methods Imaging, histological, and clinical data on patients whose first HCC was diagnosed >12 months of post‐SVR were analyzed. Histology of 20 nontumor tissues was analyzed in a blinded manner using the Knodel/Ishak/HAI system for necroinflammation and fibrosis/cirrhosis stage and the Brunt system for steatosis/steatohepatitis. Factors associated with post‐SVR HCC were identified by comparison with HALT‐C participants who did not develop post‐SVR HCC. Results Hepatocellular carcinoma was diagnosed in 54 patients (45 M/9F), a median of 6 years of post‐SVR [interquartile range (IQR) =1.4‐10y] at a median age of 61 years (IQR, 59–67). Approximately one‐third lacked cirrhosis, and only 11% had steatosis on imaging. The majority (60%) had no steatosis/steatohepatitis in histopathology. The median HAI score was 3 (1.25–4), indicating mild necroinflammation. In a multivariable logistic regression model, post‐SVR HCC was positively associated with non‐Caucasian race (p = 0.03), smoking (p = 0.03), age > 60 years at HCC diagnosis (p = 0.03), albumin<3.5 g/dL (p = 0.02), AST/ALT>1 (p = 0.05), and platelets <100 × 103 cells/μL (p < 0.001). Alpha fetoprotein ≥4.75 ng/mL had 90% specificity and 71% sensitivity for HCC occurrence. Noncirrhotic patients had larger tumors (p = 0.002) and a higher prevalence of vascular invasion (p = 0.016) than cirrhotic patients. Conclusions One‐third of patients with post‐SVR HCC did not have liver cirrhosis; most had no steatosis/steatohepatitis. Hepatocellular carcinomas were more advanced in noncirrhotic patients. Results support AFP as a promising marker of post‐SVR HCC risk.